A bigraphical model for specifying cloud-based elastic systems and their behaviour. Issue 6 (2nd November 2017) - Sahli, Hamza; Hameurlain, Nabil; Belala, Faiza
Abstract: The few recent years have witnessed the appearance of a new kind of self-adaptive systems called cloud based-elastic systems. These systems are particularly appealing for their ability to maintain a decent quality of service and reduce a system's operating cost at the same time. They achieve this by dynamically adjusting resources allocation in terms of elasticity. Meanwhile, complexity of structural and behavioural aspects related to cloud-based elastic systems increase the difficulty of designing and developing such systems. In this paper, we address this challenge by proposing a formal approach based on bigraphical reactive systems for modelling both structural and behavioural aspects of cloud-based elastic systems. In particular, we represent their behaviour in terms of client/application interactions and elasticity methods at different levels using bigraphical reaction rules. The feasibility of the proposed approach is illustrated through a motivating example running on the top of an Amazon Elastic Compute Cloud (EC2) infrastructure. Abstract : Modelling cloud-based elastic systems using bigraphical reactive systems